TERAPI RELAKSASI OTOT PROGRESIF PADA KLIEN ANSIETAS - Mad Zaini (The Indonesian Journal of Health Science, 2017)
Someone who experience physical health problems can cause mental health problem, example  anxiety.  The  purpose  of  study  to  illustrate  the  application  of  progressive muscle relaxation therapy in anxiety clients. The method used is the case analisys in anxiety clients. The amount of clients are 34 people, 23 clients given ners intervention and progressive muscle relaxation therapy. The results were found decrease the signs and  symptoms  anxiety.  Progressive  muscle  relaxation  therapy  is  recommended  a nursing therapy in anxiety. Keywords : Anxiety, progressive muscle relaxation therapy.